1987
DOI: 10.1111/j.1600-0528.1987.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of dentists and child patients during treatment

Abstract: This study is part of a larger research project which aims to analyze children's dental fear by making a detailed analysis of the behavioral interactions between dentists and anxious child patients. The behavior of 12 high- and 12 low-anxious children was recorded on videotape during two dental visits in which the children were treated by either experienced or inexperienced dentists. Results indicated a relation between the dentist's experience in treating anxious children and the behavior of child patients. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…Esse dado coaduna-se às afirmações de Prins et al 1987;Weinstein (1986) e Weinstein et al (1982, segundo as quais as condutas positivas do profissional (fornecimento de informação, compreensão das reações emocionais, uso de fantasias, entre outros) facilitam a aquisição e a manutenção de comportamentos colaborativos com o tratamento, enquanto os padrões negativos (manejo inadequado, utilização de coerção e negação dos sentimentos da criança) potencializam as reações de medo, tais como gritos, choros e protestos.…”
Section: Análise Funcional Das Interações Profissional-pacienteunclassified
See 2 more Smart Citations
“…Esse dado coaduna-se às afirmações de Prins et al 1987;Weinstein (1986) e Weinstein et al (1982, segundo as quais as condutas positivas do profissional (fornecimento de informação, compreensão das reações emocionais, uso de fantasias, entre outros) facilitam a aquisição e a manutenção de comportamentos colaborativos com o tratamento, enquanto os padrões negativos (manejo inadequado, utilização de coerção e negação dos sentimentos da criança) potencializam as reações de medo, tais como gritos, choros e protestos.…”
Section: Análise Funcional Das Interações Profissional-pacienteunclassified
“…Aparentemente, as variáveis dos profissionais não são as únicas responsáveis pelos comportamentos das crianças durante a intervenção, uma vez que eles também tiveram seu comportamento influenciado pelas condutas dessas crianças (Prins et al, 1987;Weinstein et al, 1982). As características do procedimento clínico adotado, a familiaridade com a clínica e com o odontopediatra são exemplos de outros possí-veis fatores que influenciam a cooperação da criança.…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation
“…Prins et al (11) further developed this coding system and concluded that some of the behaviours registered in their study needed to be differentiated more clearly to make the analysis more detailed. Both the inter-and intraexaminer tests yielded a high level of agreement and high weighted kappa values.…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al (10) and Prins et al (11) have previously studied behavioural interactions between the dentist and the patient, in the context of dental anxiety, with the help of video recordings of dental appointments. A more detailed way to study behaviour is to study the interaction between two persons using the marte meo therapy model (12).…”
mentioning
confidence: 99%